Clinical comparison of patients with benign urachal masses versus urachal carcinomas - Xing Bi; Zhiming Wu; Hui Han; Fangjian Zhou (Chinese Journal of Cancer, 2017)
Abstract The clinical features of 17 patients with benign urachal masses and 30 patients with urachal carcinoma treated at Sun Yat-sen University Cancer Center were analyzed retrospectively. Univariate analysis indicated that seven parameters differed significantly between the two groups. Binary logistic regression analyses showed that the rate of gross hematuria was significantly higher (P = 0.042, Exp[B] = 7.889) and the rate of fatty infiltration of the Retzius space was significantly lower (P = 0.006, Exp[B] = 0.028) in patients with urachal carcinoma than in those with benign urachal masses. Gross hematuria and fatty infiltration of the Retzius space may be indications of malignant and benign urachal masses, respectively.